The COVID-19 Pandemic and Social Work: An Action Call for Social Cohesion - Pratibha J. Mishra (Issues and Development in Health Research Vol. 4, 2021)
Given the scourge’s harmful influence on society’s underserved and devalued populations, the social work profession, more than any other, is most harmed by the raging corona virus (aka, COVID-pandemic). More importantly, the pandemic has shattered the profession’s long-standing dedication to social justice and human rights, as well as its insistence on the value of human relationships. The goal of this paper is to explain how social work and the COVID-19 epidemic are linked. While emphasising the profession’s deafening silence in the global pandemic discourse, it argues that our reaction must be urgent if our profession is to gain meaningful public value amid the current loss of life and risks to human rights. The strategies for our professional action in limiting the contagion’s effect are laid out.Our profession may continue to be called into question, first by critics, citizens, then by our client-systems, and finally by ourselves, unless we act quickly to address the world’s major concerns.